Highly effective oxidation of roxarsone by ferrate and simultaneous arsenic removal with in situ formed ferric nanoparticles. (15th December 2018) - Yang, Tao; Liu, Yulei; Wang, Lu; Jiang, Jin; Huang, Zhuangsong; Pang, Su-Yan; Cheng, Haijun; Gao, Dawen; Ma, Jun
Abstract: Roxarsone (ROX) is used in breeding industry to prevent infection by parasites, stimulate livestock growth and improve pigmentation of livestock meat. After being released into environment, ROX could be bio-degraded with the formation of carcinogenic inorganic arsenic (As) species. Here, ferrate oxidation of ROX was reported, in which we studied total-As removal, determined reaction kinetics, identified oxidation products, and proposed a reaction mechanism. It was found that the apparent second-order rate constant (kapp ) of ferrate with ROX was 305 M −1 s −1 at pH 7.0, 25 °C, and over 95% of total As was removed within 10 min when ferrate/ROX molar ratio was 20:1. Species-specific rate constants analysis showed that HFeO4 − was the dominant species reacting with ROX. Ferrate initially attacked AsC bond of ROX and resulted in the formation of arsenate and 2-nitrohydroquinone. The arsenate was simultaneously removed by ferric nanoparticles formed in the reduction of ferrate, while 2-nitrohydroquinone was further oxidized into nitro-1, 4-benzoquinone. These results suggest that ferrate treatment can be an effective method for the control of ROX in water treatment. Graphical abstract: Highlights: The rate constant of ferrate with ROX was 305 M −1 s −1 at pH 7.0, 25 °C. As(V) would be subsequently removed by the in situ formed ferric nanoparticle. Over 95% of the total-As was removed within 10 min at pH 7 [Fe(VI): ROX = 20:1]. The reaction pathway was proposed based on mass spectrum data.